2017
DOI: 10.1159/000479570
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-214 Affects Fibroblast Differentiation of Adipose-Derived Mesenchymal Stem Cells by Targeting Mitofusin-2 during Pelvic Floor Dysfunction in SD Rats with Birth Trauma

Abstract: Background/Aims: This study investigated whether microRNA-214 (miR-214) targets mitofusin-2 (Mfn2) in the process of fibroblast differentiation of adipose-derived mesenchymal stem cells (ADMSCs) during pelvic floor dysfunction (PFD) in Sprague Dawley (SD) rats with birth trauma. Methods: The ADMSCs were isolated from 4-6 week male SD rats (n = 20) and were cultured and divided into the blank, miR-214 mimic negative control (NC), miR-214 mimic, miR-214 inhibitor NC, miR-214 inhibitor, empty vector, Mfn2 over-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…It has been reported that mitofusin 2 (Mfn2), a gene related to mitochondrial fusion, is one of the target miR-214 in adiposederived mesenchymal stem cells. 18 We then measured the expression of Mfn2 in the kidney of various mice models, however, we found no difference among the groups. In mPTCs, overexpressing miR-214 had no effect on Mfn2 expression at both mRNA and protein levels (Supplementary Figure S6).…”
Section: Enhancing Mir-214 Induces Mitochondrial Dysfunction and Cellmentioning
confidence: 83%
“…It has been reported that mitofusin 2 (Mfn2), a gene related to mitochondrial fusion, is one of the target miR-214 in adiposederived mesenchymal stem cells. 18 We then measured the expression of Mfn2 in the kidney of various mice models, however, we found no difference among the groups. In mPTCs, overexpressing miR-214 had no effect on Mfn2 expression at both mRNA and protein levels (Supplementary Figure S6).…”
Section: Enhancing Mir-214 Induces Mitochondrial Dysfunction and Cellmentioning
confidence: 83%
“…It has been argued that a single miRNA can simultaneously regulate the expression of multiple genes, and one gene can be regulated by multiple miRNAs [66]. miR-214 has been previously implicated in fibroblast differentiation of adipose-derived mesenchymal stem cells by targeting MFN2 [67], and regulates the differentiation of human hair follicle stem cells and bone marrow-derived mesenchymal stem cells [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-214 is shown to increase expression of the mRNAs and proteins for elastin (tropoelastin), fibulin-5/DANCE, and LOX by targeting mitofusin-2 in the process of fibroblast differentiation of adipose-derived mesenchymal stem cells during pelvic floor dysfunction in Sprague Dawley rats with birth trauma [30]. In the present study, DCP-LA did not affect expression of the mRNAs and fibulin-5/DANCE.…”
Section: Discussionmentioning
confidence: 44%